Family relation and STR-DNA matching using fuzzy inference - Maria Susan Anggreainy; M. Rahmat Widyanto; Belawati Widjaja; Nurtami Soedarsono; Putut Tjahjo Widodo (Institute of Advanced Engineering and Science, 2019)
Deoxyribose Nucleic Acid (DNA) are the basic elements that make up a whole section of an individual. The basic elements store information that is unique to each individual and will be passed down the generations. DNA also helps in identifying the father in paternity testing, locating missing person investigations, identifying victims in mass disasters. Identiﬁcation of the victims has a problem if the comparison the father and mother no instance the victim’s parents have died or are very far away from where the victim. Therefore, it is necessary to try to identify Short Tandem Repeat (STR) Inference of live family such as sibling, grandfather/grandmother, uncle/aunt, cousin and nephew. In this paper, we performed a method to measure the similarity of human DNA proﬁles using fuzzy similarity. In this fuzzy system, DNA profile data is used as an input that stores human identity along with its DNA profile. The data entered is the result of polymerase chain reaction (PCR) identification which is an electropherogram consisting of 16 loci with two alleles for each locus. Output in this fuzzy system is the value of individual similarity with reference and with similarity levels, namely small, medium and high.